Contornos do modelo de governança tributária global da perspectiva do Brasil: a guerra fiscal e o problema do enquadramento Keynesiano-Westfaliano - Regina Flavia Moraes Duarte (2015)
The continuous search for capital attraction in the liquid modernity reveals an international scenario of intense tax competition. While countries fight against tax base erosion, the mundialized capital keeps searching for higher profitability. States, basing their actions and international interactions in a Westphalian notion of sovereignty, can not resist the impositions of globalized capital, which ends up generating several structural problems of domestic nature. Motivated by the risks of tax base erosion or by the relativization of social achievements already sedimented, international tax war is causing huge damages to the citizens of those national states, which has been observed in Brazil. Keeping in view the idea of post-Westphalian framing brought by NANCY FRASER, in the sense that the performances observed in the domestic environment can be seen as the result of an international interaction, this work intended to identify the global tax governance model developed in Brazil, to face the incursions of globalized capital and international tax competition, especially for being a developing country. From this context, it analyzes the legislative and jurisprudential aspects of foreign income taxation and of the transfer pricing methods, in order to assess the impacts of this conflict between globalized capital and territorial Westphalian State on the making of legislative and judicial decisions in Brazil. In the end, it realizes that the problem of the national regressive tax system and the corruption of the Brazilian tax system results directly from this governance model and indirectly from worldwide competitive conjecture.